Design of a Toxic Algae Harvester - Eliasson, Edwin; Haglund, Olle; Hozouri, Daniel; Wahrén, Henrik (My University, 2020)
Harmful algae blooms in lakes and seas are increasing every year. Still, sufficient technology for removal and cleanup in lakes and seas are lacking. The entailing consequences of harmful algae blooms are not only the intoxication of both humans and animals, but also the creation of hypoxic dead-zones in waters around the world. Therefore, this study aimed to explore the possibility of creating a system able to remove wild algae from lakes and seas. Additionally, the potential of producing different products based on the harvested algae was investigated. The study was divided into two parts, concept generation and algae product research. The resulting Toxic Algae Harvester features a centrifuge for separation of algae and water and a funnel combined with a pump for collecting the algae and water. Furthermore, a suitable vessel has been designed to fit all the necessary components, making it a complete system. Additionally, a rough cost analysis has been conducted and the environmental impact of operating the system has been estimated. As for the algae product, the only feasible solution with the present research was production of biogas. The reason for this being that the algae species and composition does not have to be considered when producing biogas. The combined results from this study provides a solution that can separate algae during algae blooms in an efficient way and therefore contributes to lessen the environmental impact these blooms cause. Furthermore, it reduces the economic damage on society that would otherwise result from a decrease in fishing and tourism industries caused by algae blooms. However, the economic and environmental benefits are limited in this configuration but could be increased by further development and possibly upscaling of the Toxic Algae Harvester.